Embodied Identity in a Literary Work: Analyzing Women's Body Representation in the Film ‘Imperfect’ through Simone de Beauvoir's Lens - Permatasari, Marsella Putri; Amilia, Fitri; Suaedi, Hasan; Dzarna, Dzarna (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
As a prominent medium within the realm of literary works, film serves as a popular medium with a strong influence on public perceptions of various phenomena and issues, particularly as media act as conduits for societal control in the modern era. This study aims to explore the representation of women's bodies in the film Imperfect by Ernest Prakasa through the lens of Simone de Beauvoir's existentialist feminist theory. The research focuses on two main aspects: societal beauty standards for women's bodies and the female protagonist's resistance to these standards. Imperfect portrays the social pressures women face to conform to narrow, patriarchal standards of beauty, such as a slim figure and fair skin. The study employs a descriptive qualitative method, with data collection techniques including observation and note-taking. Observation is conducted through attentive viewing of the film, while note-taking involves documenting relevant dialogues and scenes. Data analysis is carried out systematically in several stages: transcribing key scenes, identifying and classifying scenes that reflect beauty standards and the concept of